2018
DOI: 10.1002/hbm.24274
|View full text |Cite
|
Sign up to set email alerts
|

Neural specialization of phonological and semantic processing in young children

Abstract: This study aimed to examine early specialization of brain regions for phonological and semantic processing of spoken language in young children. Thirty-five typically developing children from 5- to 6-years of age performed auditory phonological (same sound judgment) and semantic (related meaning judgment) word-level tasks. Using functional Magnetic Resonance Imaging, we examined specialization within the language network, by conducting three levels of analysis. First, we directly compared activation between ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 113 publications
(354 reference statements)
10
56
3
Order By: Relevance
“…Thus, our findings suggest that IFG sub-regions are specialized in early childhood for phonological processing but not for semantic categorization. We did not find specialization of temporal sub-regions as observed by Weiss et al (2018), which might be attributed to the modality of stimuli, visual-only stimuli (this study) versus audio-only stimuli (Weiss et al 2018).…”
Section: Fronto-temporal Lobecontrasting
confidence: 65%
See 3 more Smart Citations
“…Thus, our findings suggest that IFG sub-regions are specialized in early childhood for phonological processing but not for semantic categorization. We did not find specialization of temporal sub-regions as observed by Weiss et al (2018), which might be attributed to the modality of stimuli, visual-only stimuli (this study) versus audio-only stimuli (Weiss et al 2018).…”
Section: Fronto-temporal Lobecontrasting
confidence: 65%
“…However, our study does not show evidence for temporal specialization for the phonological processing and fronto-temporal specialization for the semantic processing. On the contrary, using an auditory rhyme and semantic judgment tasks, Weiss et al (2018) reported the specialization for the phonological processing in the left STG and SMG, and the specialization for the semantic processing in the left MTG by the age of 5-6-years. Some differences between our findings and results from Weiss et al (2018) could be attributed to modality of stimuli.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Recently, Weiss et al (2018) conducted one of the first investigations to date exploring whether language-related neural specialization is observable in young children. Specifically, the authors examined whether 5.5-to-6.5 year old children showed evidence of distinct brain regions uniquely supporting phonological over semantic processing (or alternatively semantic over phonological processing).…”
Section: Introductionmentioning
confidence: 99%